REGUŁA PIERWOTNA ZAKONU UBOGICH RYCERZY CHRYSTUSA I ŚWIĄTYNI SALOMONA - Kamil Wasilkiewicz (In Gremium. Studies in History, Culture and Politics, 2012)
THE LATIN RULE OF THE POOR KNIGHTS OF CHRIST AND THE TEMPLE OF SOLOMONThe Latin Rule of the Knights of the Temple of Solomon was created between 1119 and 1128. It was written, edited and approved during the synod in Troyes in January 1128 and included 72 articles referring to the most important issues for the Knights Templars. The content of the Latin Rule was clearly influenced by st. Bernard from Clairvaux as many of parts it resemble the Cisterian rule. The document was in force for over a decade. In 1140 it was supplemented with new content and translated into French. These changes led to the creation of a new Rule, known as the French rule, which brought the functioning of the Latin Rule to an end.